Inhibition, transition, and surge: dynamic evolution of pediatric respiratory pathogen trends amid COVID-19 pandemic policy adjustments - Xu, Xuena; Pan, Zhenzhen; Dong, Heting; Zhang, Yizhu; Xu, Lina; Wang, Pengli; Wang, Yufeng; Li, Jiaoyang; Jiang, Wujun; Hao, Chuangli (Frontiers in Public Health, 2024)
Background: The implementation of a zero-COVID policy for 3 years in China during the COVID-19 pandemic significantly impacted a broad spectrum of acute respiratory tract infections (ARTIs).The epidemiological characteristics of ARTI pathogens in children following the cessation of the zero-COVID policy remain unclear.Methods: Etiologically diagnostic data from 82,708 children with ARTIs at the Children's Hospital of Soochow University during 2016-2023 were analyzed for 8 pathogens (human respiratory syncytial virus [HRSV], influenza A [FluA], FluB, human parainfluenza virus [HPIV], adenovirus [ADV], human rhinovirus [HRV], bocavirus [BoV], and mycoplasma pneumoniae [MP]). The changes in respiratory infections in Suzhou, China during the first year (2020, Phase I) and the second and third years of the pandemic (2021-2022, Phase II) and the first year after the end of zero-COVID policy (2023, Phase III) versus that in the pre-pandemic years (2016-2019) were compared.Results: When compared with the average pre-pandemic levels, the pathogen-positive rate decreased by 19.27% in Phase I (OR: 0.70; 95% CI: 0.67-0.74), increased by 32.87% in Phase II (OR: 1.78; 95% CI: 1.72-1.84), and increased by 79.16% in Phase III (OR: 4.58; 95% CI: 4.37-4.79). In Phase I, the positive rates of HRSV, FluA, ADV, and MP decreased by 26.72%, 58.97%, 72.85%, and 67.87%, respectively, and the positive rates of FluB, HPIV, HRV, and BoV increased by 86.84%, 25%, 32.37%, and 16.94%, respectively. In Phase III, the positive rates of HRSV, FluA, FluB, HPIV, ADV, and HRV increased by 39.74%, 1046.15%, 118.42%, 116.57%, 131.13%, and 146.40%, respectively, while the positive rate of BoV decreased by 56.12%. MP was inhibited during the epidemic, and MP showed a delayed outbreak after the ending of the zero-COVID policy. Compared with the average pre-pandemic levels, the MP-positive rate in Phase III increased by 116.7% (OR: 2.86; 95% CI: 2.74-2.99), with the highest increase in 0-1-year-old children. The strict and large-scale implementation of the zero-COVID policy in the early stages of the COVID-19 pandemic was the main driving factor for the sharp reduction in the rate of children's respiratory pathogenic infections. The termination of this policy can cause a resurgence or escalation of pathogenic infections.